Mbopo Initiation Rite in Ibibio: Ibibio Cultural Heritage - Nana, Aniekan Etim; Umanah, Aniefiok Effiong (NIU Journal of Social Sciences; Vol 9 No 1 (2023): NIU Journal of Social Sciences, Vol. 9 No. 1, March 2023DO - 10.58709/niujss.v9i1.1605, 2023)
In Ibibio pre-colonial time, Mbopo culture was found to be practiced in every family, it was a pride of every young maiden then to be initiated in this cultural institution, without which the person will not be regarded in the society. Mbopo institution was highly rated and esteemed in Ibibio pre-colonial era. The aesthetic aspect of the Mbopo was the fundamental principles found in Mbopo culture. This paper investigates reasons for the sudden negligence this cultural heritage in some of the Ibibio communities which was a pride to the people, in respect to checking the moral behaviour of young girls then. This paper shall equally examine the concept of Mbopo initiation, mode of feeding, fattening preparation and ceremonial outing of Mbopo in Ibibio land. This work shall adopt analytical method in tackling the Mbopo initiation rite. Although the practice has some ill effect, this study recommends that good values should be upheld for the continuity of Ibibio cultural heritage. Keywords: Mbopo, Rite, Ibibio, Cultural Heritage